"The Gentle Spirit" - E. Gaškienė-Červinskienė (Literatūra (Vilnius), 1975)
The article deals with one of Dostoyvsky's most characteristic works so far but little elucidated by critics. The poliphonic structure of the story makes it necessary for the investigator to search for the writer's message very carefully. The idea of the work is revealed on the basis of all the elements of the story, including its genesis.